2010
DOI: 10.1007/s12603-010-0106-x
|View full text |Cite
|
Sign up to set email alerts
|

Waist-to-height ratio, an optimal predictor for obesity and metabolic syndrome in Chinese adults

Abstract: The results indicated that WHtR might be an optimal anthropometric predictor of metabolic syndrome risk factors and the cut-point of WHtR was approximately 0.50 in both genders of Chinese adults.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
56
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(69 citation statements)
references
References 26 publications
12
56
0
1
Order By: Relevance
“…Several studies on Asian [3], [4], [5], [6] and Caucasian [32], [38] populations have found WHtR to be superior to WC in identifying cases with cardiovascular risk factors. Meta-analyses provide further confirmation of those findings [33], [39].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies on Asian [3], [4], [5], [6] and Caucasian [32], [38] populations have found WHtR to be superior to WC in identifying cases with cardiovascular risk factors. Meta-analyses provide further confirmation of those findings [33], [39].…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, controversy remains over which anthropometric parameter best defines obesity and conveys the highest risk of cardiometabolic disturbance. In recent years, waist-to-height ratio (WHtR) has been regarded as the best screening tool for detecting cardiometabolic risk factors, especially in Asians [3], [4], [5], [6]. Some studies have proposed the use of waist circumference (WC) or waist-to-hip ratio (WHR) [7], [8], [9], whereas others advocate their combined use [10], [11].…”
Section: Introductionmentioning
confidence: 99%
“…The WC though proposed to be better than BMI in measuring obesity, because it captures abdominal obesity does not reflect fat mass that may be distributed in non-abdominal tissues-a major demerit of the tool (Lean et al, 1995). The WHtR has been shown to be a good predictor of adiposity-related disorders such as the metabolic syndrome (Shao et al, 2010). It is nonetheless limited because "The WC measurement assesses only visceral adiposity such that dividing it by the subject's height wrongly distributes the fatness localized around the abdomen to the entire body" (Ejike and Ijeh, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, lean body mass is negatively associated with all-cause mortality (35). When this fact is coupled with the knowledge that WHtR is a predictor of MetS (36), it seems reasonable to suggest that, for a given WHtR value, a higher hip circumference may not indicate an increased health risk. Addressing this issue could have important implications for determining the manner in which WHtR and hip circumference are used to predict metabolic disorders in both research and the clinical settings.…”
Section: Discussionmentioning
confidence: 99%